2018
DOI: 10.1037/sgd0000272
|View full text |Cite
|
Sign up to set email alerts
|

Bisexual women’s discrimination and mental health outcomes: The roles of resilience and collective action.

Abstract: Using an additive intersectional perspective, this study examined the roles of antibisexual discrimination and sexist experiences in relation to bisexual women’s psychological distress and well-being. In addition, group- (i.e., feminist and lesbian, gay, bisexual, transgender, and queer [LGBTQ] collective action) and individual-level (i.e., resilience) protective factors were examined in these respective links. A total of 304 predominantly White, bisexual women participated in this study. At the bivariate leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 59 publications
(130 reference statements)
4
35
2
4
Order By: Relevance
“…We conducted a structural equation model power analysis (Soper, 2019) to evaluate the adequacy of our sample size. We used the following parameters to conduct the analysis: desired power of .80, six latent variables, 20 items/observed indicators, α = .05, and a conservative minimum standardized path estimate of .25 (between small and medium effect; Soper, 2019) based on prior research yielding medium to large correlations between the variables of interest (e.g., Johnson et al, 2005; Moradi & Funderburk, 2006; Perez et al, 2012; Saunders & Kashubeck-West, 2006; Watson, Morgan, & Craney, 2018; Wright et al, 2010; Yoder et al, 2012). This calculation suggested that the minimum sample size of 156 for our model structure and 246 for detecting effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a structural equation model power analysis (Soper, 2019) to evaluate the adequacy of our sample size. We used the following parameters to conduct the analysis: desired power of .80, six latent variables, 20 items/observed indicators, α = .05, and a conservative minimum standardized path estimate of .25 (between small and medium effect; Soper, 2019) based on prior research yielding medium to large correlations between the variables of interest (e.g., Johnson et al, 2005; Moradi & Funderburk, 2006; Perez et al, 2012; Saunders & Kashubeck-West, 2006; Watson, Morgan, & Craney, 2018; Wright et al, 2010; Yoder et al, 2012). This calculation suggested that the minimum sample size of 156 for our model structure and 246 for detecting effects.…”
Section: Resultsmentioning
confidence: 99%
“…Studies focusing specifically on women’s feminist collective action and feminist personal empowerment also link these forms of empowerment with women’s well-being. For example, feminist collective action was correlated positively with well-being in a sample of predominantly White bisexual women (Watson, Morgan, & Craney, 2018). In an experimental study with racially and ethnically diverse college women, well-being increased over three days for women assigned to a feminist collective action via social media condition but not for those assigned to control conditions (Foster, 2015).…”
Section: Feminist and Critical Consciousness Theories And Women’s Welmentioning
confidence: 99%
“…Kwon’s (2013) review of literature on resilience identified three factors that promote health and well-being in LGB populations: social support, the ability to accept and process emotions, and hope and optimism. Other reviews have also identified individual level protective factors (such as positive identity), but concurrently emphasize the importance of interpersonal factors (such as family/intimate relationship strengths and connectedness to LGBT communities) and larger community and structural contexts such as access to LGBT community resources, advocacy for affirming laws and policies, and influencing social norms and attitudes (de Lira & de Morais, 2017; Hatzenbuehler & Pachankis, 2016; Hill & Gunderson, 2015; Lyons, 2015; Meyer, 2015; Watson, Morgan, & Craney, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such symbolic social justice acts, although not without contention, recognize the within-group diversity among the LGBTQþ community and raise awareness of the issues affecting specific LGBTQþ communities. Last, engaging in social justice advocacy initiatives has also been found to relate to better well-being for LGBTQþ people (Velez & Moradi, 2016;Watson, Morgan, & Craney, 2018), and therefore clinicians, teachers, and advocates should recognize that advocacy has both societal and individual benefits. Levitt (2019) provides numerous examples of the ways in which LGBTQþ gender and gender expression have developed in response to the social and political conditions of the time, as well as how it has challenged rigid social norms through subversive and liberatory acts.…”
Section: Psychosocial Theory Of Gender Inmentioning
confidence: 99%